Determination of Lipoprotein Z-Specific IgA in Tuberculosis and Latent Tuberculosis Infection - Xiao, Jia-ni; Xiong, Yanqing; Chen, Yingying; Xiao, Yang-jiong; Ji, Ping; Li, Yong; Wang, Shu-jun; Zhao, Guo-ping; Cheng, Qi-jian; Lu, Shui-hua; Wang, Ying (Frontiers in Cellular and Infection Microbiology, 2017)
Tuberculosis (TB) remains one of the most severe infectious diseases. It is still of paramount importance to establish more accurate, rapid and efficient diagnostic methods. Since infection with Mycobacterium tuberculosis (M. tb) is largely mediated through the respiratory tract, IgA responses against mycobacterial proteins are worthy of investigation for their potential clinical utility. In this study, the IgA response targeting lipoprotein Z (LppZ) was determined by using a homemade ELISA with plasma of TB patients (N=125), LTBI individuals (N=92), healthy controls (HCs) (N=165) as well as TB patients undergoing anti-TB treatment (N=9). In parallel the antigen-specific IFN- release from PBMCs triggered by LppZ and M. tb-specific ESAT-6 or CFP-10 was detected by using an ELISPOT assay. It was found that the LppZ-specific IgA level was dramatically higher in TB patients than in HCs (p < 0.0001). Compared to that before anti-TB treatment, the LppZ-specific IgA level decreased substantially after 2 months of anti-TB treatment (p=0.0297) and remained at low levels until the end of the treatment. What is more, pulmonary TB patients exhibited significantly higher LppZ-specific IgA values than extra-pulmonary TB patients (p=0.0296). Interestingly, the LppZ-specific IgA values were negatively correlated to the amounts of IFN- released in response to LppZ with statistical significance (r=-0.5806, p=0.0002). LppZ-specific IgA level was also higher in LTBI individuals than in HCs (p < 0.0001). Additionally there were some PPD+ HC individuals with high LppZ-specific IgA levels but the potential of this assay for identifying leaky LTBI in PPD+ HCs needs to be further investigated through follow-up studies. The sensitivity of detecting TB solely with ESAT-6 or CFP-10-specific IFN- release was increased by including the LppZ-specific IgA results, respectively from 86.11% to 100% and 88.89 to 100%; the sensitivity of screening for LTBI was increased from 80.36% to 83.93% and 57.14% to 69.64% respectively. The higher LppZ-specific IgA responses in TB and LTBI populations than in controls indicated high immunoreactivity to LppZ upon M. tb infection. Although the assay was not efficient enough for independent application in sero-diagnosis, LppZ-specific IgA might become a complementary biomarker for the improvement of TB and LTBI screening.